Core/Shell and Multi-Scale Structures Enhance the Electrocatalytic Oxygen Reduction Reaction of the PdSn@Graphene Nano-Composites in an Alkaline Condition - Gong, Wenzhao; Chen, Chengmeng; Kong, Qingqiang; Wang, Mao-Zhang; Weny, Yue-Fang; Liu, Lang; Yang, Yonggang (Asian Journal of Chemistry, 2012)
The core/shell electrocatalyst of PdSn nanoparticles supported on graphene was reported. Morphology, crystallinity and elements content of the synthesized materials were investigated by X-ray diffraction (XRD), transmission electron microscope (TEM) and energy dispersive X-ray (EDX), respectively. The results showed that the graphene support highly and homogeneously dispersed PdSn nanoparticles at the different soaking times. Catalyst activity for oxygen reduction reaction in an alkaline condition was investigated by cyclic voltammetry (CV). The fundamental electrochemical test results indicated that PdSn@graphene nano-composites could be considered a much better electrocatalyst material for use in alkaline fuel cell cathode materials.